Literature Review: Sintesis Cost-Volume-Profit, Balanced Scorecard, dan Corporate Governance - Rahmat Hidayat; Aristanti Widyaningsih; R Nelly Nur Apandi (Yayasan Literasi Sains Indonesia, 2025)
This study examines in depth the integration between Cost-Volume-Profit, Balanced Scorecard, and Corporate Governance in the context of corporate strategic decision-making. The purpose of this literature review is to analyze how Cost-Volume-Profit, Balanced Scorecard, and Corporate Governance are interrelated in the context of strategic decision-making in various industry sectors. This study uses a literature review approach by collecting and analyzing previous studies related to Cost-Volume-Profit, Balanced Scorecard, and Corporate Governance. Through a literature review of 30 research articles, it was found that the implementation of Cost-Volume-Profit, Balanced Scorecard, and Corporate Governance simultaneously provides significant benefits for companies. This study only uses secondary data from published articles. Therefore, the study did not involve the collection of primary data such as surveys or direct interviews. The results of this study show that companies that implement these three tools synergistically can achieve improved financial and non-financial performance, ensure long-term sustainability and create value for shareholders. Further research is needed to explore the practical application of this integration in different industry sectors, in order to find out the specific benefits in each sector.